Semiochemicals and odorant receptors underlying potato cultivar susceptibility and resistance to potato tuber moth - Ruipeng Chen; Wangtao Hu; Qin Hu; Junjie Yan; Jiao Yin; Fathiya M. Khamis; Yulin Gao; Walter S. Leal (Proceedings of the National Academy of Sciences, 2026)
Infestation of potato by the potato tuber moth ( Phthorimaea operculella ) varies markedly among cultivars, yet the chemical and molecular mechanisms underlying this variation remain poorly understood. Here, we combine field surveys, chemical ecology, functional genomics, and structural modeling to reveal how cultivar-specific volatile profiles shape moth oviposition behavior and pest outcomes. Field and laboratory assays identified marked differences in adult attraction, oviposition, and larval damage among potato cultivars, which correlated with distinct blends of emitted volatile organic compounds (VOCs). Behavioral analyses revealed that among other VOCs, trans -nerolidol and β-ionone act as attractants, whereas 3-carene and benzyl tiglate function as oviposition deterrents. Electrophysiological screening and heterologous expression deorphanized six female-biased odorant receptors (ORs), identifying three narrowly tuned receptors linked to cultivar susceptibility or resistance. PopeOR01, upregulated following mating, selectively detects the attractant trans -nerolidol, which is enriched in susceptible cultivars, whereas PopeOR15 and PopeOR73 are tuned to repellents benzyl tiglate and 3-carene, respectively, which are enriched in resistant cultivars. CRISPR/Cas9-mediated knockouts confirmed that PopeOR01 and PopeOR73 are essential for antennal detection and behavioral responses to their cognate ligands. AlphaFold3 modeling, molecular docking, and molecular dynamics simulations revealed conserved OR-Orco channel architecture and stable ligand-binding modes consistent with physiological and behavioral data. Together, our results establish a mechanistic link between potato cultivar chemistry, insect olfactory receptor function, and pest behavior, providing a molecular framework for sustainable, semiochemical-based management of the potato tuber moth.